2000
DOI: 10.1385/bter:78:1-3:93
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Supplements' Effect on Potassium Balance in Athletes During Prolonged Hypokinetic and Ambulatory Conditions

Abstract: Electrolyte supplements may be used to prevent changes in electrolyte balance during hypokinesia (diminished movement). The aim of this study was to measure the effect of potassium (K) supplements on K balance during prolonged hypokinesia (HK). Studies were done during 30 d of a pre-HK period and during 364 d of an HK period. Forty male athletes aged 25.1+/-4.4 yr were chosen as subjects. They were divided equally into four groups: unsupplemented ambulatory control subjects (UACS), unsupplemented hypokinetic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 10 publications
2
20
0
Order By: Relevance
“…It is consistent with prior studies [11][12][13][14] where during the preexperimental period, K + homeostasis, plasma K + level, and urine and fecal K + loss were relatively stable regardless of the amount of K + consumed. This shows that in the pre-experimental period, the K + consumed during supplementation has been used up for deposition and was taken by the body which protected the net muscle K + content, plasma K + level, and urine and fecal K + loss without showing any gross differences in the experimental and control groups of subjects.…”
Section: Discussionsupporting
confidence: 92%
“…It is consistent with prior studies [11][12][13][14] where during the preexperimental period, K + homeostasis, plasma K + level, and urine and fecal K + loss were relatively stable regardless of the amount of K + consumed. This shows that in the pre-experimental period, the K + consumed during supplementation has been used up for deposition and was taken by the body which protected the net muscle K + content, plasma K + level, and urine and fecal K + loss without showing any gross differences in the experimental and control groups of subjects.…”
Section: Discussionsupporting
confidence: 92%
“…During a normal muscular activity, K + depletion develops because of the decreased K + consumption, excessive K + losses through gastrointestinal tract and kidney, and a redistribution of K + within the body due to insulin intake, and magnesium depletion. However, K + depletion during prolonged HK is much more complicated, because K + depletion is present with and without K + supplementation, and K + depletion is accompanied by a significant increase of plasma K + level [5][6][7][8][9] and K + losses [5][6][7][8][9]. Using K + supplementation to normalize K + depletion during prolonged HK had shown that K + is neither entering nor being retained by muscles, where most K + is normally deposited.…”
Section: Introductionmentioning
confidence: 99%
“…Using K + supplementation to normalize K + depletion during prolonged HK had shown that K + is neither entering nor being retained by muscles, where most K + is normally deposited. This shows the presence of another mechanisms and primarily the presence of decreased K + deposition, that may lead to significant increase of K + losses with K + imbalance and consequently may contribute to the development of K + depletion in healthy subjects during prolonged HK [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations